Functional and component structure of the population trading service system - Кобилін, П. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Formulation the problem. Over the past decade the system of population trading service has seen substantial qualitative changes, particularly the ownership form of retail, restaurant business institutions changed, the range of products expanded, new types of stores, forms of trade (supermarkets, hypermarkets, shopping malls, internet commerce, vending machines etc.) appeared. These changes affect the functional and component structure of population trading service system that has become more complicated. All it needs is detailed study, clarification of the conceptual and terminological apparatus. Scientific literature highlights theoretical and practical aspects of the population trading service. There are many classifications of retail, restaurant business institutions, products. However, there is lack of references regarding system approach to understanding the population trading service.The aim of the publication is to highlight features of the functional and component structure of population trading service system. Research results. Conceptual and terminological apparatus to study the system of population trading service forms such as: trade, trading activity, trading complex of the administrative region, population trading service, trade and restaurant industry infrastructure. Functional and component structure of the system of population trading service consists of subsystems of retail trade, restaurant industry, and service enterprises. Retail trade is formed by shops, semi-stationary objects of retail trade, markets, trade not in stores, shopping malls, which have branched structure. Restaurant industry consists of cafes, bars, restaurants, canteens, buffet, snack bars, cafeterias, supply of finished food. Service enterprises are finance and credit, research and design, transport, insurance, logistic, security, maintenance and engineering, accounting, legal, informational, repair and construction, transportation and other ones. The classifications of retail trade and restaurant industry institution were developed by various criteria: by shape, type, degree of sustainability location, ownership, size, service frequency, prices level, product range, location, etc. Goods were classified by frequency demand, frequency and mode of storage, manufacturing site, frequency use, seasonality, raw sign, etc.Scientific novelty. Based on the concept of the social and geographicl system and system approach in human geography the definition of "system of population trading service" has been proposed as a functional component of the social and geographical system. Based on the model of socioactogenezis the technological scheme of satisfying social needs through the system of population trading service was created by the author which includes four successive stages: social needs awareness, creating the system of goals, formation of the executive system, and getting results. The system of population trading service is a part of the executive system, and a link in the goods movement from producer to consumer, it connects supply and demand of goods.